Analisis Temporal Suhu Permukaan Laut di Perairan Indonesia Selama 32 Tahun (Era AVHRR) - Putra, I Nyoman Januarta Triska; Karang, I Wayan Gede Astawa; Putra, I Dewa Nyoman Nurweda (Journal of Marine and Aquatic Sciences, 2019)
One of the important factor that influences global climate dynamics is sea surface temperature (SST). Indonesian waters are semi-closed and located between the Pacific and Indian Oceans so that they have different characteristics of SPL in each region. The purpose of this research is to know the trend and local characteristics of Indonesian SST and adjacent areas in response to 6-monthly and seasonal variability with moving average method and correlation. The data used are SST data from AVHRR satellite with domain 15°N-15°S, 90°-145° E. The results showed of increase trend 0.34°C in Indonesian sea for 32 years (1981-2012). The characteristics of SST in Indonesian territory are closely related to the Mosoon cycle where in the East period in the northern region the Natuna Sea is warmer in contrast to the West monsoon period, in the southern part of the Arafura Sea to the warmer Sawu Sea and around the equator experiencing the warmest in the transitional period. The moving-average analysis shows that 6-monthly variability appears to be dominated in equatorial waters including the Java Sea and Banda Sea whereas seasonal variability occurs in the northern and southern regions of Indonesia's waters including the Pacific Ocean Oceans, the northwest Pacific Ocean and the southeast Indian Ocean. Based on correlation analysis, ENSO has a strong (negative) relationship in eastern Indonesia waters including the Sea in the northern part of Papua and the northwest Pacific Ocean while IOD has a strong (negative) relationship in the western Sumatra Sea, Banda Sea and Arafura Sea.